Selenium Nanoparticles Improved Intestinal Health Through Modulation of the NLRP3 Signaling Pathway - Chen, Yanhong; Wu, Wei; Zhou, Huajin; Liu, Xingbo; Li, Shu; Guo, Yanbing; Li, Yuxin; Wang, Yongqiang; Yuan, Jianmin (Frontiers in Nutrition, 2022)
Selenium nanoparticles (SeNPs) play important roles in promoting animal health whereas its impacts on intestinal health remain elusive. This study was intended to evaluate the effect of different doses of SeNPs on the intestinal health, especially the development of goblet cells in broiler jejunum. A total of 480 1-day-old Arbor Acres broilers were randomly allotted to 5 treatments with being applied to 6 replicates of 16 chicks each. Birds were fed with low selenium corn-soybean meal-based diets supplemented with 0.0, 0.1, 0.2, 0.3, or 0.4 mg/kg of SeNPs. On d 21, dietary supplemental SeNPs could effectively reduce the mortality of broilers. The villus height and the villus height/crypt depth of jejunum showed significantly quadratic curves with increasing the concentration of SeNPs (P < 0.05). The mRNA expression of zonula occluden-1 (ZO-1), ZO-2, claudin-3, claudin-5 in the jejunum decreased significantly linearly with the increasing dose of SeNPs (P < 0.05). The mRNA expression levels of interleukin 1 beta (IL-1β), IL-18 and the concentration of reactive oxygen species (ROS) in the jejunum decreased significantly linearly with the increase of SeNPs concentration (P < 0.05). Compared with the control group, the number of goblet cells in the jejunum were significantly increased by adding 0.1 and 0.4 mg/kg SeNPs(P < 0.05). In addition, the mRNA expression of Mucin2(Muc2) showed a significant quadratic curve relationship that increased after adding 0.1 mg/kg SeNPs(P < 0.05). Dietary SeNPs also decreased significantly linearly the expression of v-myc avian myelocytomatosis viral oncogene homolog(c-myc) (P < 0.05). The mean density of TUNEL positive cells in 0.2 and 0.4 mg/kg SeNPs group were highly significantly lower than control group (P < 0.05). Similarly, the mRNA expression levels of B-cell lymphoma-2 (Bcl-2), Bcl2-associated X (Bax), NLR family pyrin domain containing 3(NLRP3), cysteinyl aspartate specific proteinase-1(Caspase-1), toll-like receptor-2 (TLR-2), myeloid differentiation factor88 (MyD88) in the jejunum decreased significantly linearly with the increase of SeNPs concentration (P < 0.05). Our results show that supplemental SeNPs can decrease intestinal oxidative stress and inflammation by modifying the activation of NLRP3 signaling pathway, which can effectively promote intestinal morphology and goblet cells of 21-day-old broilers.